(untitled) (International Journal of Irrigation and Water Management, 2014)
A ‘farmer-centric’ innovative institutional mechanism, a public-private partnership, was created and strengthened, in the Fergana valley of Central Asia, for facilitating communication between farmers and researchers, and to disseminate knowledge on improved agronomic and irrigation management practices to improve water productivity at field level. As a result, yields of cotton from the twenty five demonstration sites in the three countries of Fergana valley - Kyrgyzstan, Tajikistan and Uzbekistan – were, on the average, 28% higher than the average yield of cotton in the valley, suggesting that the proposed institutional mechanism was very effective in dissemination of information to farmers. Yields from neighboring farmers of demonstration fields were 14% higher than the average yields. In addition, demonstration site farmers used, on the average, 20% less water than the non-project farmers. Two independent external reviewers stated that this innovative public-private mechanism was very effective in disseminating information on improving water productivity at plot level to farmers, and suggested that the focus in the future should be on devising effective policy and economic instruments for financial sustainability of the innovation cycle after the donor support is withdrawn.